IDENTIFIKASI KERUSAKAN POHON PINUS DI HUTAN KOTA BANJARBARU - Halim Kerta Negara; Normela Rachmawati; Damaris Payung (Jurnal Sylva Scienteae, 2020)
This research is done to identify Pine tree damage in Banjarbaru’s urban forest, analyze the most founded damage causes in Pine tree at Banjarbaru’s urban forest and count Pine tree damage percentage. Method which used in this research is census with observing all Pine tree in Mentaos I Pine’s urban forest. Results that have been obtained in this research is the most found damage cause is weather which can make result in broken branch, meanwhile the most found damage type is open wounded at stem before branch. The most founded crown condition has percentage 30-39%. Percentage of damage frequency that has been obtained is 75.4% so that from all Pine trees which have been observed so many damaged well in big or small scale.Keywords: damage, frequency, percentage, Pine tree